In vitro Regeneration and Agrobacterium-mediated Genetic Transformation of Tomato (Lycopersicon esculentum Mill.) (Plant Tissue Culture and Biotechnology, 2010)
Agrobacterium-mediated genetic transformation system has been developed for two tomato (Lycopersicon esculentum Mill.) varieties, namely Pusa Ruby (PR) and BARI Tomato-3 (BT-3). Prior to the establishment of transformation protocol cotyledonary leaf explants from the two varieties were cultured to obtain genotype independent in vitro regeneration. Healthy multiple shoot regeneration was obtained from the cut ends of cotyledonary leaf segments for both the varieties on MS containing 1.0 mg/l BAP and 0.1 mg/l IAA. The maximum root induction from the regenerated shoots was achieved on half the strength of MS medium supplemented with 0.2 mg/l IAA. The in vitro grown plantlets were successfully transplanted into soil where they flowered and produced fruits identical to those developed by control plants. Transformation ability of cotyledonary leaf explants was tested with Agrobacterium tumefaciens strain LBA4404 harboring binary plasmid pBI121, containing GUS and npt II genes. Transformed cotyledonary leaf explants were found to produce multiple shoots on MS containing 1.0 mg/l BAP and 0.1 mg/l IAA. Selection of the transformed shoots was carried out by gradually increasing the concentration of kanamycin to 200 mg/l since kanamycin resistant gene was used for transformation experiments. Shoots that survived under selection pressure were subjected to rooting. Transformed rooted plantlets were transferred to soil. Stable expression of GUS gene was detected in the various tissues from putatively transformed plantlets using GUS histochemical assay.  Key words: In vitro regeneration, transformation, tomato D.O.I. 10.3329/ptcb.v19i1.5004 Plant Tissue Cult. & Biotech. 19(1): 101-111, 2009 (June)